1956
DOI: 10.1103/physrev.103.662
|View full text |Cite
|
Sign up to set email alerts
|

Fission Neutron Spectrum ofU235

Abstract: The neutron spectrum associated with the fission of U 235 induced by slow neutrons has been remeasured from 0.18 to 12 Mev. Two different experimental techniques were employed in this measurement: (1) the time-of-flight method covering the energy range from 0.18 to 2.7 Mev, and (2) the photographic plate method encompassing the energy range from 0.35 to 12 Mev. The combined results of these measurements fit the relation, N{E)^Ke^E' QMh sinh[(2.29£)»], where N(E) is the neutron flux, E is the neutron energy in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1963
1963
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(19 citation statements)
references
References 5 publications
1
18
0
Order By: Relevance
“…83 data points have been selected from the simulation results that covering the energy range from 10keV to 14MeV to be used for analysis. The cubic polynomial is expressed as formula (2)…”
Section: Fig1part Of the Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…83 data points have been selected from the simulation results that covering the energy range from 10keV to 14MeV to be used for analysis. The cubic polynomial is expressed as formula (2)…”
Section: Fig1part Of the Simulation Resultsmentioning
confidence: 99%
“…It has been amongthe earliestparticle detectors used in high-energy physics and has inherent advantages when detecting neutrons in high energy [1]. Neutrons can be detected via recoil proton tracks in the nuclear emulsion and the neutron energy spectrum can then be determined from length distribution of the tracks [2,3]. To determine the energy of each incident neutron with respect to the proton recoil trajectory, the usual procedure is to accept proton recoils within a given angular criteria, measure the projection in the plane of the emulsion of the ranges of the recoil protons, and make an average correction to the deduced neutron energies.When using the nuclear recoil method to detect neutrons, most of the energy of the neutrons are passed to the recoil protons.Especially when the incident neutronsimpact on thenuclear emulsion planeperpendicularly, energy of the recoil protons roughly equal to that of the incident neutrons.…”
Section: Introductionmentioning
confidence: 99%
“…A number of researchers seem to have proposed this shape, which was probably first reported in the literature by Watt, when he documented his measurements on fission-neutron spectra. Cranberg et al (1956), who reported on extended measurements some years later, also discuss this representation of the neutron spectrum. The Watt spectrum can be described by…”
Section: Prompt Neutron Spectramentioning
confidence: 99%
“…of each reaction is proportional to the product of the reaction cross section, o, and the number of incident neutrons, n, at that energy. The value of n was taken from Cranberg et al [12] The effective range of o.-particles with energy of 0.32 MeV was determined, and the helium released within this distance of the surface of the beryllium was compared with the total gas produced and measured.…”
Section: Calculation Of Average Alpha Particle Energymentioning
confidence: 99%